Gasdermin-D driven pyroptosis fuels oxidative stress in ulcerative colitis: Biochemical and physiological correlations - T. H. Mgheer; H. H. K. Al-Shukri; H. H. Naji; Z. H. Kadhim; A. H. Khudhair; T. H. Salih (Regulatory Mechanisms in Biosystems, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease, resulting from intricate interplay among immune dysregulation, epithelial barrier malfunction and oxidative stress. Recent evidence has identified pyroptosis, a lytic and inflammatory type of programmed cell death, which is mediated by g asdermin D (GSDMD), as an important driver of intestinal inflammation. Pyroptosis also results in the release of proinflammatory cytokines, such as IL-18, that can further activate neutrophils and increase oxidative damage. Nevertheless, there are few integrated clinical research studies on the simultaneous detection of pyroptosis and cyt o kine release and oxidative stress markers in UC. Thus the aim of our research is to determine the serum concentrations of GSDMD, IL-18, myeloperoxidase (MPO), malondialdehyde (MDA) and C-reactive protein (CRP) in UC patients compared with healthy controls and to investigate their relationships as well as explore the diagnostic value of these indices for UC. Methods : A case-control study was performed with 45 patients who were diagnosed with UC and 45 age-matched healthy controls. Serum levels of GSDMD, IL-18, MPO, and MDA were assayed by enzyme linked immunosorbent assay (ELISA), and C-reactive protein (CRP) was assessed with immunodetection methods. Statistical analysis comprised independent t-tests, correlation, receiver operating characteristic (ROC) curve and logistic regression. Results : The concentration of serum GSDMD, IL-18, MPO, MDA and CRP in UC patients we re all obviously higher than that in controls (all P < 0.05). IL-18 was positively correlated with CRP (r = 0.481, p = 0.001) and MDA (r = 0.389, p = 0.008). The ROC analysis showed excellent diagnostic power for GSDMD (AUC = 0.993), IL-18 (AUC = 0.995), and MDA (AUC = 0.992) in distinguishing UC patients from healthy controls. In regression analysis, GSDMD and IL-18 were independent predictors for UC status. Conclusions : Together, these results favor a pathogenic model of UC where GSDMD-mediated pyroptosis leads to IL-18 release and subsequent neutrophil activation and oxidative lipid damage. GSDMD, IL-18 and MDA show promise as alternative non-invasive diagnostic markers. These findings emphasize the importance of both pyroptosis and oxidative stress next to other biological mechanisms in their translation into clinical aspects of UC.